Changes in Cannabis Consumption During the Global COVID-19 Lockdown: The International COVISTRESS Study - Salles, Juliette; Yrondi, Antoine; Marhar, Fouad; Andant, Nicolas; Dorlhiac, Raimundo Avilés; Quach, Binh; Jiao, Jiao; Antunes, Samuel; Ugbolue, Ukadike Chris; Guegan, Julien; Rouffiac, Karine; Pereira, Bruno; et al. (Frontiers in Psychiatry, 2021)
Introduction: COVID-19 lockdown measures have been sources of both potential stress and possible psychological and addiction complications. A lack of activity and isolation during lockdown are among the factors thought to be behind the growth in the use of psychoactive substances and worsening addictive behaviors. Previous studies on the pandemic have attested to an increase in alcohol consumption during lockdowns. Likewise, data suggest there has also been a rise in the use of cannabis, although it is unclear how this is affected by external factors. Our study used quantitative data collected from an international population to evaluate changes in cannabis consumption during the lockdown period between March and October, 2020. We also compared users and non-users of the drug in relation to: 1) sociodemographic differences, 2) emotional experiences, and 3) the information available and the degree of approval of lockdown measures. Methods: An online self-report questionnaire concerning the lockdown was widely disseminated around the globe. Data was collected on sociodemographics and how the rules imposed had influenced the use of cannabis and concerns about health, the economic impact of the measures and the approach taken by government(s). Results: 182 respondents consumed cannabis before the lockdown versus 199 thereafter. The mean cannabis consumption fell from 13 joints per week pre-lockdown to 9.75 after it (p<0.001). Forty-nine respondents stopped using cannabis at all and 66 admitted to starting to do so. The cannabis users were: less satisfied with government measures; less worried about their health; more concerned about the impact of COVID-19 on the economy and their career; and more frightened of becoming infected in public areas. The risk factors for cannabis use were: age (OR=0.96); concern for physical health (OR=0.98); tobacco (OR=1.1) and alcohol consumption during lockdown (OR=1.1); the pre-lockdown anger level (OR=1.01); and feelings of boredom during the restrictions (OR=1.1). Conclusion: In a specific sub-population, the COVID-19 lockdown brought about either an end to the consumption of cannabis or new use of the drug. The main risk factors for cannabis use were: a lower age, co-addictions and high levels of emotions.